QUALITY OF WAITERS SERVICE ON BREAKFAST SESSION IN THE CAFE HOTEL PREMIERE PEKANBARU - Rani Anggraini; Andi M. Rifiyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The purpose of this research is to know the quality of service waiters at The Cafe Hotel Premiere Pekanbaru, to know the factors apasaja affect waiters service at breakfast session at The Cafe Hotel Premiere Pekanbaru.This research uses descriptive quantitative method to analyze the problem. The sample used is 100 respondents and the data obtained using questionnaires, observations, and interviews. By using Likert scale as a tool to determine the length of the interval.Based on the research results, the quality of waiters service at breakfast session at The Cafe Hotel Premiere Pekanbaru consisting of five indicators are: Tangible, Emphaty, Responsiveness, Assurance, Reliability. The least good service is on ResponsivinessKeywords: Service, Breakfast, Waiters, food and Beverage, and Restaurant.